Between International Coffee Chain and Indonesia Local Coffee Chain: the Differences on Driving Factors for Customer Satisfaction and Loyalty - Bagus Kalijaga; Ardhianiswari Diah Ekawati (Cakrawala Repositori IMWI, 2024)
The aim of this research is to identify factors that influence customer loyalty, including service quality, product quality, software quality, price fairness, atmosphere, and brand image with the mediation of customer satisfaction between customers of international coffee chains in Indonesia and Indonesian local coffee chains. The research was conducted on Starbucks Indonesia and Kopi Kenangan customers with a total of 448 respondents. Multigroup Analysis and Partial Least Square Structural Equation Modeling (PLS-SEM) are used to test validity, reliability and variable testing. The test results show that each coffee shop has several differences in the factors that influence customer satisfaction and loyalty, but store atmosphere is found to be the main driving factor that can influence customer satisfaction and loyalty in international coffee chains or Indonesian local coffee chains. This research is the first study to integrate service quality, product quality, software quality, price fairness, atmosphere, brand image, customer satisfaction and customer loyalty by comparing international coffee chains and Indonesian local coffee chains.